What is a Collection? - Curral, James; Moss, Michael; Stuart, Susan (Archivaria, 2004)
The word "collection" has been common currency in what we accept as the real world of objects and events, and has been imported with seemingly little effort into our discourse about the digital world, yet there is no clear definition in either domain of what is meant by the term. We clarify this issue by first examining how the term is used in the contemporary information science literature and then by going on to establish the criteria which are employed in bringing a collection about. We will argue that the assumption that there is a realist permanence or fixity in the world that determines taxonomies is false, and that the only feasible approach to the construction of categories to which objects, whether digital or physical, are allocated is an anti-realist one where attention is paid to the intentions and subsequent decisions of the collector. RÉSUMÉ Le mot "collection" est monnaie courante dans le monde réel des objets et des événements et a été importé sans trop d’efforts dans notre discours sur le monde numérique. Cependant, il n’en existe pas de définition précise dans aucun de ces domaines. Les auteurs clarifient ce problème en examinant d’abord comment ce mot a été utilisé dans la littérature contemporaine sur les sciences de l’information et ensuite en établissant les critères qui sont employés pour créer une collection. Ils allèguent que l’hypothèse qu’il existe une permanence au sens réaliste du terme ou une fixité dans le monde qui détermine la classification est fausse. Selon eux, la seule approche faisable dans la construction de catégories pour répartir des objets, qu’ils soient numériques ou physiques, est anti-réaliste, et on doit alors porter attention aux intentions et aux décisions de l’institution qui collectionne.